Faktor Yang Mempengaruhi Kinerja Keuangan (Studi Kasus UMKM Kuliner Kota Yogyakarta) - Anggreini, Maharani; Maulida, Alfiatul; Prima Sari, Pristin (Journal of Economics, Bussiness and Management Issues, 2024)
Economic growth in Indonesia is increasing with the emergence of Micro, Small, and Medium Enterprises (MSMEs) that offer a variety of products, one of the most popular types of businesses in Indonesia is in the culinary sector. The purpose of this study is to determine the influence of access to capital, financial literacy, compiling financial reports and payment gateways on the financial performance of culinary MSMEs in Yogyakarta City. This study uses a quantitative method with primary data obtained from the distribution of questionnaires, respondents are obtained in accordance with the sampling technique, namely using the slovin formula and data that has been in accordance with the calculation, namely 100 respondents. The results of this study show that the variables of access to capital and compiling financial statements have a positive and insignificant effect on financial performance, while the variables of financial literacy and payment gateway have a positive and significant effect on financial performance. Therefore, increasing access to capital, financial literacy, compiling financial reports and payment gateways are the basic capital needed by culinary MSME actors in order to minimize risks in management or decision-making in improving financial performance.